(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Micro Combined Heat and Power (Micro CHP) refers to small-scale installations that generate heat, electricity or both connected to the low voltage distribution network at the customer side. Although the connection of the Micro CHP to the low-voltage distribution networks improves security of supply, there are many operational challenges such as stability and control. This paper study the stability of synchronous generator connected to reciprocating engine as one type of Micro CHP. Also, a several studies have been done to investigate the response of Small scale embedded generation (SSEG) to a range of network faults and thereby ascertain the range of conditions under which SSEG might be expected to trip. Many of these may be regarded as nuisance trips when the action of network protection does not isolate the SSEG from a mains supply. Any protection associated with the SSEG has not been included in order to demonstrate inherent capability and response. The critical clearing time (CCT) is used to indicate the stability of the SSEG. In this investigation the CCT of the SSEG is calculated and simulated using Power Systems Computer Aided Design PSCAD/EMTDC as well as from the mathematical calculations.